Catalysts and barriers to increasing the consumption of fruits and vegetables and reducing the prevalence of hypertension: Monitoring metrics, dietary quality, and farmland capacity. - Conrad, Zach. (2017)
Abstract: Hypertension is a prominent risk factor for cardiovascular disease (CVD), which is the leading cause of death in the United States (US). Adequate consumption of fruits and vegetables (F&V) is associated with a reduced risk of developing hypertension and CVD, yet most Americans do not meet the recommended daily consumption amounts for F&V. National public health goals for 2020 include increasing the consumption of F&V and reducing the prevalence of hypertension, but several barriers stand in the way of achieving these goals. Three different dietary data collection programs are used to inform nutrition policies, interventions, and messages, but the degree of agreement among the data generated by these programs has not been examined. Additionally, although the Dietary Approaches to Stop Hypertension (DASH) diet - which includes high amounts of F&V - is associated with a reduced risk of hypertension, CVD, and all-cause mortality, the rate of adherence continues to be low. Finally, most F&V consumed in the US are produced domestically, but the capacity of the US agricultural system to accommodate increased consumption of nutrient dense F&V is not well documented. The goal of this dissertation is to examine several catalysts and barriers to achieving the national public health nutrition goals of increasing the consumption of F&V and reducing the prevalence of hypertension; this will be accomplished through three separate studies. In the first study, I estimate the comparability of daily per capita F&V consumption data generated from the National Health and Nutrition Examination Survey (NHANES), 2007-2010; the Behavioral Risk Factor Surveillance System (BRFSS), 2007-2011; and the Loss-Adjusted Food Availability (LAFA) data series, 2007-2011; using statistical agreement tests and descriptive means comparisons. In the second study, I develop a food pattern model to examine whether consuming nutrient dense F&V, instead of those currently consumed, without increasing the amount consumed, will provide enough fiber, calcium, magnesium, and potassium for hypertensive adults to meet the nutrient targets of the DASH diet. In the third study, I create geospatial models to investigate the degree to which the US agricultural system can increase the production of selected nutrient dense F&V in eleven major production centers. The results of these studies are as follows. In the first study, I found that NHANES, BRFSS, and LAFA do not produce the same results and should not be used interchangeably to estimate daily per capita F&V consumption at the national level. In the second study, I found that consuming nutrient dense F&V instead of those currently consumed, without increasing the amount consumed, will not provide enough nutrients for hypertensive adults to meet the nutrient targets of the DASH diet; yet by choosing more nutrient dense F&V and increasing the number of servings consumed, hypertensive adults can meet the nutrient targets with fewer servings than is recommended. In the third study, I found that there is enough suitable agricultural land within the major production centers to accommodate a substantial increase in demand for selected nutrient dense F&V, but that further increases in the per capita availability of F&V are needed for hypertensive adults to meet the DASH diet. This research is important for several reasons. It shows that matching the research question to the appropriate data source is essential to computing accurate estimates of daily per capita consumption of F&V. This research also provides clinicians with information that can be used to help their hypertensive patients adopt more healthy dietary patterns. Finally, this research highlights the important role that smaller production centers and international food markets will play if hypertensive adults adopt healthier eating patterns.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Agriculture, Food and Environment.; Advisor: Timothy Griffin.; Committee: Christian Peters, and Kenneth Chui.; Keywords: Nutrition, Public health, and Agriculture.